STATISTICAL APPROACH TO EVALUATE HELICOPTER COMPETITIVENESS AT THE EXTERNAL DESIGN PHASE AND WHILE MAKING A DECISION TO PURCHASE A HELICOPTER - V. T. Bobronnikov; I. Yu. Nikulina (Научный вестник МГТУ ГА)
The methodology of helicopter competitiveness evaluation based on statistical data on volume of sales dynamics in money terms and performance of helicopter modifications has been developed. Competitiveness factor calculated as linear convolution of sum of production of helicopter parameters weight numbers determined on the basis of correlation between the helicopter parameters and annual helicopter sales in money terms and its normalized values have been introduced. The methodology can be applied on the helicopter external design phase and while taking a decision about a helicopter purchase. The results of numerical computations are given to demonstrate the methodology.